System and Procedure for Providing Wholesales Incentives at PT Krama Yudha Tiga Berlian Motors Dealers - Alifi Herdini, Sabila; Anggraini, Asterina (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2024)
Keeping sales stable and increasing is difficult. The Parts Business Development Department is the division that has responsible for spare part sales at PT Krama Yudha Tiga Berlian Motors (KTB) for creating a Wholesales Incentive Program to motivate dealers in selling spare parts. The research method used was observation and interviews with several employees of the Parts Business Development Department to find out the types of incentives used, various procedures, and problems that occurred in the Wholesales Incentive Program process. The results of the research are an incentive program that uses is SODEXO vouchers and a several procedures carried out to make Wholesales Incentive Program runs smoothly by setting realistic targets and incentive formulas. The implementation of the Wholesales Incentive Program by following procedural guidelines is expected to produce output that meets expectations.